Islam, Memory, and Morality in Yemen: Ruling Families in Transition by Gabriele vom Bruck (New York: Palgrave, 2005. 348 pages.) (American Journal of Islam and Society, 2006)
The anthropological literature on Yemen has had little to say about the classof sadah (plural of sayyid) who dominated the Zaydi imamate in NorthYemen from the tenth century until 1962. Gabriele vom Bruck’s account ofthe sadah, based on interviews and an extended stay in Yemen starting in1983, includes a wide range of information on perceptions of this class,especially after the 1962 revolution, with an emphasis on how personal identityis established and attitudes about marriage with non-sadah. There is anextensive bibliography of western sources, but little indication of the widerange of relevant Arabic sources available. It should be noted that vomBruck almost totally ignores the sadah of southern Yemen as well as of theTihama, although her text sometimes reads as if it were describing a genericclass of sadah for Yemen as a whole. The author’s stated goal is “to examine the relationship of experience,social practice, and moral reasoning among the hereditary elite in the contextof revolutionary change” (p. 5). Her theoretical focus is on the social processof remembrance as the sadah were forced into new roles after the imamate’sdemise. Vom Bruck argues that we should avoid “a monolithic understandingof sayyid as a ‘vessel of charisma’ and ‘paragon of piety’” (p. 250) and suggeststhat the “descent metaphor” (p. 6) was the “principle self-defining criterion”of the sadah as well as the “core of the Imamate’s political culture.”(p. 6) However, the idiom of descent has also been the defining feature ofYemen’s tribes, so the role of descent per se is less relevant as a distinguishingmarker than how the sadah relate to other social categories.Although the relationship with tribesmen is mentioned at several points,it is not analyzed in depth apart from anecdotal evidence. For example, it ishighly problematic to label musicians al-akhdam (p. 44), who were actuallyquite rare in Zaydi towns and villages, a nuanced pariah category. There islittle sense of how the sadah fit into actual communities, and no effectiveintegration of the available literature previously published on Yemeni socialcategories (including Tomas Gerholm’s Market, Mosque, and Mafraj [StockholmUniversity Press: 1977] and Eduard Glaser’s important late-nineteenthcentury articles) ...